Early coronary angiography after out-of-the-hospital cardiac arrest without ST-segment elevation : systematic review protocol - Alves, Nuno; Mota, Mauro; Ribeiro, Joana; Cunha, Madalena (Millenium - Journal of Education, Technologies, and Health, 2021)
Introduction: Coronary artery disease is an important cause of out-of-the-hospital cardiac arrest (OHCA) and coronary angiography often plays a major role in its management. While in the presence of ST-segment elevation (STE) CAG is mandatory within the first 2h, in no-STE OHCA patients there is no consensus on whether early CAG should be performed by default. Objetives: To assess the impact of early CAG (<24h) in no-STE OHCA patients. Methods: Herein is described the protocol of a systematic review, which will be developed according to the methodology proposed by the Joanna Briggs Institute. The studies will be analysed and selected for inclusion by two independent reviewers. Results: The primary endpoint will be short-term survival and the secondary endpoints will include survival with favourable neurological outcomes, mid-term survival and renal adverse events, ventricular arrhythmias and bleeding during hospital stay. This study will analyse and synthetize the evidence concerning the performance of early CAG in no-STE OCHA patients in the context of current clinical practice. Conclusion: Our results will allow a better planning and standardization of care for no-STE OHCA patients.